Responsible leadership : global and contextual ethical perspectives - Stuckelberger, Christoph; Mugambi, Jesse N. K (WCC Publications, 2007)
"With a range of well-respected voices from across the business, political, third sector and research spectrum, this important book provides an accessible insight into responsible leadership. It represents the most comprehensive and informed work on responsible leadership linked to the UN SDGs produced to date. This carefully edited volume, based on a collaborative partnership between the Institute for Responsible Leadership (IRL) and the United Nations Institute for Training and Research (UNITAR), contains twenty chapters in seven parts which address the relationship between responsible leadership and the UN Sustainable Development Goals. These original and accessible contributions discuss progress in a variety of areas relevant to the goals, including climate change and biodiversity, global health, cybercrime, human trafficking, corporate social responsibility, gender, education, and social cohesion. The world-leading expert contributors are drawn from a wide range of societies and continents, and cover key aspects of responsible leadership in lively and impactful fashion. This book is for leaders at every level in the public, private and third sectors, students concerned with responsible leadership, academics and researchers studying leadership in different disciplinary fields, and all those committed to sustainable development and progressing the UN SDGs"--